Comparative sequence analysis of rotavirus genomic segment 6--the gene specifying viral subgroups 1 and 2. - Both, G W (1984)
Cloned DNA copies of rotavirus genomic segment 6 from simian 11 (subgroup 1) and human strain Wa (subgroup 2) rotaviruses have been used to determine the nucleotide sequences of the gene that determines viral subgroup specificity. Both genomic segments are 1,356 nucleotides in length and possess 5'- and 3'-terminal untranslated regions of 23 and 142 nucleotides, respectively. The inferred amino acid sequence reveals VP6 to be a polypeptide of 397 amino acids in which more than 90% of the amino acid sequence is conserved between the two viruses. There are 34 amino acid changes between the subgroup 1 and 2 polypeptides, most clustered in three regions of the molecule at residues 39 through 62, 80 through 122, and 281 through 315.